ASSESSMENT OF RISK OF INFECTION RELATED TO SURFACE CONTAMINATION AND EQUIPMENT IN A HOSPITAL IN THE CITY OF FEZ (CENTER OF MOROCCO) - EL OUALI LALAMI ABDELHAKIM,; EL-AKHAL FOUAD,; OUMOKHTAR BOUCHRA, (International Journal of Pharma and Bio Sciences, 2015)
Nosocomial infections are a major cause of complications and health care are now, a major concern in hospitals. The objective of this work, realized for the first time, is to evaluate the microbiological quality of surfaces and equipment used in three services to potential infectious risks (intensive care, pediatric and hemodialysis). This study was conducted over a period of two months (February-March) of 2009. Thus, a total of twenty-eight samples (28) were recovered from various points in the three services studied. Species identification was based on microbiological and biochemical tests. We have identified bacteria of human and environmental origin have a major nosocomial risk such as: Acinetobacter baumannii, Pseudomonas aeruginosa, coagulase negative Staphylococci and Klebsiella sp. respectively with a percentage of about 33%, 26%, 17% and 8%. The isolation of these microorganisms varies from one service to another. These results require corrective action represented mainly by rigorous cleaning procedures. These must be included in a comprehensive policy management and prevention of nosocomial infections.